Tsunami hazard assessment for the central and southern pacific coast of Colombia. Issue 4 (1st October 2020) - Escobar, Ronald Sanchez; Diaz, Luis Otero; Guerrero, Anlly Melissa; Galindo, Milton Puentes; Mas, Erick; Koshimura, Shunichi; Adriano, Bruno; Urra, Luisa; Quintero, Paola
ABSTRACT: Highly destructive tsunamis occurred near the Pacific coast of Colombia in 1906 and 1979. Recent studies have established asperities within the subduction zone in this area, which can cause megathrust earthquakes triggering highly destructive tsunamis. In this study we assess the tsunami hazard in the main populated areas of Colombia Pacific coast by calculating the inundation depth and the maximum tsunami height from major scenario. A deterministic method is applied using slip deficit models and broadband slip models as tsunami sources. Result suggest that, for the worse-case scenario, the maximum deformation of the seafloor is 6.0 m within the Esmaraldas segment ; the maximum height of the tsunami is 4.66 m, 4.34 m and 0.53 m around. Tumaco Island, Morro Island, and Cascajal Island (Buenaventura Bay), respectively. Two to five meters inundation depth were calculated in over 11% and 10% of the total areas of the islands of Tumaco and Morro, respectively. Based on these result, tsunami hazard maps were alaborated and will serve to create tsunami mitigation plans in these areas.